Digital multimedia perception and design - Ghinea, Gheorghita; Chen, Sherry Y.; Gale Group (Hershey, Penn. Idea Group Publishing, 2006)
"This book provides a well-rounded synopsis of the state-of-the-art in perceptual-based multimedia design"--Provided by publisher.
Foreword -- Preface -- Section I: Perceptual modeling in multimedia -- Section II: Multimedia and the five senses -- Section III: Human factors -- Section IV: Multimedia communication and adaptation -- About the authors -- Index.
Electronic reproduction.
Keywords: Multimedia systems; System design; Perception; Electronic books